Investigating Professional Development Policy and Practice for Educational Policy-Makers in Vietnam: An Exploratory Study (Journal of Contemporary Educational Policies and Practices, 2024)
There has been a large number of studies concerning professional development at the micro level. However, little research has been particularly conducted to investigate professional development at the macro level. This study aims to explore professional development policy and practice in a Vietnamese government department. Using a qualitative with two focus group discussions including 11 participants and semi-structured interviews with 14 people, the study investigates professional development for state policy-makers in testing and quality assurance in Vietnam. Results show that these government officials themselves actively looked for professional development programmes together with receiving support from their organisational leaders. The research findings also reveal that top-down and bottom-up professional development mechanisms are being implemented. However, professional development policy has not been documented in this government agency. It is suggested that professional development policy aligned with best practices should be discussed, developed and evaluated by agency members and soon approved by the agency’s leader.